Governance challenges for Indonesian pond aquaculture: a case study of milkfish production in Gresik - Riany, Citra Fitrie; Partelow, Stefan; Nagel, Ben (Frontiers in Aquaculture, 2023)
Introduction An important blind spot in current aquaculture governance research and practice is recognizing the high dependency of the sector on commons (i.e., shared resources), and their interconnectivity with other sectors such as agriculture. This is particularly evident in Indonesia where there is general lack of social and governance research on aquaculture. The purpose of this study is to: (1) identify the commons that need to be governed in pond aquaculture systems, and (2) identify the arising governance challenges from those commons and potential solutions. Methods We apply Elinor Ostrom’s Socio-Ecological Systems Framework (SESF) to identify variables influencing collective action through semi-structuredinterviews with relevant key informant actors in a milkfish aquaculture village in Gresik, Indonesia. Our case study approach allows for a rich description through qualitative data to understand system interactions. We interviewed 22 stakeholders including regional and local government officials, fish farmers (owners and workers), patrons and local academics. Results and discussion Our findings indicate five governance challenges influencing collective action: (1) limited access to capital and dependence on patrons, (2) lack of govern institutions, (3) continued government program failure, (4) lack of community leadership, and (5) lack of motivation and incentives to collectively act. These imply that governance policies may be more successful if monitoring mechanisms are applied to ensure that government funding is more precisely targeted at improving the livelihoods of traditional fish farmers. Furthermore, attempts to support social capital, network structures, and improve trust-reciprocity among relevant stakeholders (i.e., farmers, extension officers, private business actors) in the form of capacity building is likely more effective than other monetary incentives or the enforcement of top-down rules that don’t fit local needs.